uORF-mediated translational regulation of the human PERK mRNA - Fernandes, Rafael (2020)
Upstream open reading frames (uORFs) are cis-acting elements located within the 5’ leader sequence (5’UTR) of transcripts, which can regulate translation of the correspondent main open reading frame (mORF). During endoplasmic reticulum (ER) stress, the accumulation of unfolded proteins activates the ER-resident PKR-like ER kinase (PERK), which results in phosphorylation of eIF2α to inhibit global mRNA translation, while allowing the selective uORF-mediated translation of downstream effectors responsible for stress resolution or, ultimately, cell death. The dual role of PERK in regulating cell fate was implicated in human diseases, like diabetes, neurodegenerative disorders and cancer. Moreover, mutations in the EIF2AK3 gene (encoding PERK) were associated to the rare genetic disease, Wolcott-Rallison Syndrome (WRS). In this work, we aimed to study the translational regulatory role of 5 AUG- and 3 non-AUG-uORFs identified in the PERK 5’UTR and assess its biological relevance. While uORF2 and the non-AUG-uORFs 5, 6 and 7 (numbered according to their distance to the 5’ end of the mRNA) do not seem to have a regulatory role, uORF1, uORF3, uORF4 and uORF8 together present a strong repressive effect over mORF translation in basal conditions. Curiously, we found that when PERK is overexpressed, it leads to the spontaneous activation of a portion of PERK in the absence of any stress stimulus, possibly highlighting the biological relevance of its uORF-mediated translational regulation. Conversely, during ER stress, increased bypass of uORF1 results in a modest degree of translational de-repression, which may help to counterbalance the increased rate of PERK protein turnover observed in these conditions. We also observed that alteration of the PERK uORFs by mutations found in WRS patients modify mORF expression, providing a possible link to the disease. Altogether, we highlight the importance of including 5’UTRs in the screening of disease-related mutations and the necessity of functional studies to assess their role in pathogenesis.